The Factors Causing Work Fatigue among Nurses after COVID-19 Vaccination - Alfid Afandi; Dicky Endrian Kurniawan; Kholid Rosyidi Muhammad Nur; Anisah Ardiana; Nurfika Asmaningrum; Retno Purwandari (Babali Nursing Research, 2024)
Introduction: Work fatigue is a risk for all workers, including nurses, who are constantly working to help meet patient needs. The effects of work fatigue when providing nursing care to patients can have an impact on reducing the quality of work so that it can impact patient satisfaction in receiving services. The aims of the study are to determine the factors that cause work fatigue in nurses after the COVID-19 vaccination program.